Invisible geography on the Internet. - Kitchin, Rob; Sykes, Lisa (Geographical (Geographical Magazine Ltd.))
Offers advice on the various means of accessing the Internet. History of the Internet; Hardware and software requirements; Average cost of subscribing with a commercial service provider; Software packages to access the World Wide Web; Use of a `search engine,' the computer equivalent of the Yellow Pages; Telnet and FTP; Electronic mail.